Sustainability Benefits and Their Pass-on to Consumers under Article 101(3) TFEU : A Study on Sustainability Benefits and the Revised Pass-On to Consumers Doctrine in the Commission’s 2022 Draft Revised Guidelines for Application of Article 101 TFEU on Horizontal Co-operation Agreements - Pälsi, Oiva (My University, 2023)
This thesis concerns the Commission’s draft Guidelines on the applicability of Article 101 of the Treaty on the Functioning of the European Union to horizontal cooperation agreements for the part of the new chapter on sustainability agreements. It is a humble legal study on the field of EU competition law. The thesis aims to assess if the treatment of sustainability agreements and the acceptance of sustainability benefits under the Article 101(3) TFEU as well as the revised pass-on to consumer doctrine in the Commission’s Draft Revised Guidelines, have changed from the historical perspective, and to identify theoretical weaknesses of the proposed evaluation scheme of these benefits under the Draft Revised Guidelines. Both fundamental and technical problems concerning individual non-use value benefits and collective benefits doctrine are discussed. The study is theoretical and is carried out mostly by legal dogmatic method. Main sources for the thesis include both primary and secondary sources of EU law, academic literature as well as written contributions to the Commission’s public consultation on the draft revised horizontal guidelines. The main findings of the thesis are that consideration of non-economic, including sustainability, benefits under the Article 101(3) TFEU regime is not a genuinely new phenomenon. Neither is the collective benefits doctrine proposed in the draft revised guidelines. The thesis also identifies issues with the non-use value benefits and considers them a faulty and meaningless design. It is also argued that the collective benefits doctrine is liable to be create unjustifiable geographical limitations to sustainability agreements’ useful application and that the proposed doctrine is in conflict with the polluter pays principle prescribed by Article 191(2) TFEU. The thesis concludes that in order to overcome the most significant issues identified with the Commission’s draft revised guidelines in relation to sustainability agreements, individual non-use value benefits should be deleted from the guidelines and the definition of beneficiaries of collective benefits should be clarified and broadened. It could also be clarified that sustainability benefits that are significant enough to have a global or societal impact, can accrue to consumers in the relevant market even if the direct beneficiaries can be localized outside the EU.

Tutkielma käsittelee komission luonnosta suuntaviivoiksi Euroopan unionin toiminnasta tehdyn sopimuksen 101 artiklan soveltamiselle horisontaalisiin yhteistyösopimuksiin sen uuden kestävän kehityksen sopimuksia koskevan luvun osalta. Kyseessä on vaatimaton oikeustieteellinen tutkimus EU:n kilpailuoikeuden alalla. Tutkielman tavoitteena on arvioida kestävää kehitystä koskevien sopimusten kohtelua, kestävän kehityksen tehokkuushyötyjen SEUT 101(3) artiklan mukaista hyväksymistä sekä näiden hyötyjen kuluttajille siirtämistä koskevaa muutosta komission suuntaviivojen luonnoksessa historiallisesta perspektiivistä ja osoittaa ehdotetun tehokkuushyötyjen arviointijärjestelmän teoreettisia heikkouksia. Teksti käsittelee niin perustavanlaatuisia kuin teknisiäkin yksilöllisiä muita kuin käyttöarvohyötyjä sekä kollektiivisia hyötyjä koskevaan doktriiniin liittyviä ongelmia. Tutkielma on teoreettinen ja enimmäkseen lainopillinen. Pääasiallisina lähteinä tutkielmassa ovat niin EU:n primaari- kuin sekundaarilainsäädäntö, akateeminen kirjallisuus kuin myös komission ehdottamien suuntaviivojen luonnosta koskevaan julkiseen konsultaatioon toimitetut kirjalliset näkemykset. Tutkielman pääasialliset päätelmät ovat, ettei muiden kuin taloudellisten, mukaan lukien kestävää kehitystä koskevien, tehokkuushyötyjen huomioon ottaminen SEUT 101(3) artiklan mukaisesti ole varsinaisesti tuore ilmiö. Myöskään kollektiivisten hyötyjen huomioiminen suuntaviivoiksi ehdotetun luonnoksen mukaisesti ei sitä ole. Tutkielmassa myös tunnistetaan yksilöllisiin muihin kuin käyttöarvohyötyihin liittyviä ongelmia ja todetaan niiden olevan huonosti suunniteltu ja hyödytön tehokkuushyötykategoria. Tutkielmassa niinikään väitetään, että kollektiivisia hyötyjä koskeva doktriini on omiaan luomaan epäoikeudenmukaisia maantieteellisiä rajoituksia kestävää kehitystä koskevien yhteistyösopimusten tarkoituksenmukaiselle hyödyntämiselle ja että ehdotetun kaltainen doktriini on ristiriidassa SEUT 191(2) artiklassa säädetyn saastuttaja maksaa -periaatten kanssa. Tutkielman lopputulema on, että selvittääkseen merkittävimmät kestävän kehityksen yhteistyösopimuksia koskevat komission suuntaviivojen luonnoksesta löydetyt ongelmat, tulisi suuntaviivoista jättää pois yksilöllisiä muita kuin käyttöarvohyötyjä koskeva tehokkuushyötykategoria, ja selkeyttää sekä laajentaa hyötyjien käsitettä. Voitaisiin myös selventää, että silloin kun saavutettavat hyödyt ovat riittäviä ollakseen tunnistettavia globaaleiksi tai yhteiskunnallisiksi, ne voivat aina siirtyä merkityksellisillä markkinoilla oleville kuluttajille, vaikka suorat hyötyjät olisivatkin maantieteellisesti EU:n ulkopuolella.
Keywords: EU law, Competition law, Horizontal co-operation agreements, Sustainability